2008
DOI: 10.1159/000137681
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Stem Cells to Kidney Repair

Abstract: The potential role of stem cells in the repair of glomerular and tubular injury is under intensive investigation. Several studies have addressed the role of endogenous bone-marrow (BM)-derived stem cells (SC) in the repair of renal injury. Some reports indicate that BM-derived SC are capable of engraftment into damaged nephrons, although the lineage of SC recruited has not been established. However, this issue remains highly controversial, and several studies point to a paracrine/endocrine action of endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 175 publications
5
81
0
1
Order By: Relevance
“…Recent studies have ascribed reparative effects of MSCs to their endocrine/paracrine functions [15][16][17][18][19]. MSCs can generate different cytokines and growth factors that are important to injury recovery [17,57,62,63], including renotrophic factors IGF-1 and HGF (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have ascribed reparative effects of MSCs to their endocrine/paracrine functions [15][16][17][18][19]. MSCs can generate different cytokines and growth factors that are important to injury recovery [17,57,62,63], including renotrophic factors IGF-1 and HGF (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs generate an array of cytokines and growth factors [15,56] that protect kidneys from injuries [15][16][17]57]. Therefore, we postulated that 14S,21R-diHDHA treatment enhanced the beneficial effects of MSCs by augmenting their secretion of renotrophic factors.…”
Section: S21r-dihdha Treatment Enhances Mmsc and Hmsc Secretion Ofmentioning
confidence: 99%
“…In the second half of gestation, the AF is constituted by fetal urine, gastrointestinal excretions, respiratory secretions, and substances exchanged through the sac membranes [14][15][16].…”
Section: Amniotic Fluid (Af): Function Origin and Compositionmentioning
confidence: 99%
“…The dose of HgCl 2 was determined in accordance with preliminary experiments and corresponds to a lethal dose 90% (LD90). We determined the serum mercuric concentration by atomic absorption spectrophotometer PerkinElmer 1.100 B (PerkinElmer, Shelton, CT) at different time points (3,6, and 12 h).…”
Section: Animals and Induction Of Atnmentioning
confidence: 99%
“…4,5 Recent experimental data have indicated that bone marrow cells migrate to the kidney lesions, ameliorate renal function, and reduce tubular injury in AKI, through differentiation within the tubular compartment and by secreting growth and trophic factors. 6 In addition, infusion of bone marrow-derived mesenchymal stem cells may contribute to improvement of kidney lesions by a paracrine action. 7 Therefore, cell therapy utilizing adult bone marrow-derived cells has appeared as an alternative therapeutic strategy to treat renal diseases.…”
Section: Introductionmentioning
confidence: 99%